Promoting peace and harmony through inter-religious dialogue : Malaysia experience - 2000 to 2017 - Suraya binti Mohamed Yasin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study attempts to explore the framework of inter-religious dialogue in Malaysia as well as how it promotes to the peace and harmony of multi-religious society in Malaysia. The main goal of this research is to provide a unique framework for inter-religious dialogue to be used by the members of Malaysia's multi-religious society. This research is very significant as it helps those involved in inter-religious activities to have better understanding of each other's religious values. This research employs qualitative method. It will study the historical background about the establishment of Inter-Religious Dialogue in Malaysia. This study will apply descriptive method, especially in those parts that examine the historical background of Malaysian community, Inter-Religious Dialogue and its types. Also, this research will apply the analytical method to explore the role of Inter-Religious Dialogue in promoting peace and harmony to Malaysia. The researcher also conducted a brief face-to-face interview with the student president of an organization in higher educational institution, IIUM. The results of this study show that inter-religious dialogue as the best platform to promote peace and harmony in Malaysia's multi-religious society and serves as a vehicle to strengthen the good relationship between adherents of religious backgrounds in Malaysia. Recommendations include: a center for inter-religious dialogue program to be establish, a proper module of inter-religious dialogue to be follow by the participants of inter-religious dialogue and to develop the best framework or manual of inter-religious dialogue in Malaysia.